2022
DOI: 10.1002/ijgo.14192
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of routine first‐trimester combined screening for preeclampsia based on the Gaussian algorithm: A clinical effectiveness study

Abstract: Objective: To evaluate the clinical effectiveness of the routine first-trimester screening for preeclampsia (PE) after being implemented in six Catalan maternities. Methods: Participants in the reference group were recruited prospectively between October 2015 and September 2017. Participants in the study group were recruited retrospectively between November 2018 and May 2019, after implementing the screening program. PE risk was assessed between 11 + 0 and 13 + 6 weeks of gestation using the Gaussian algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…All included studies were carried out in high‐income settings, potentially reflecting access to early pregnancy care and ultrasound as part of algorithm‐based first‐trimester screening assessments. Six articles reported outcomes following screening linked to preventative therapy in unselected populations of singleton pregnancies 26,28–32 . One study reported outcomes related to prophylactic therapy within a sub‐set of women who had screened high risk 27 ; this was matched with a subsequent publication regarding the screening outcomes of the same population to establish event rates across the entire unselected cohort 33 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies were carried out in high‐income settings, potentially reflecting access to early pregnancy care and ultrasound as part of algorithm‐based first‐trimester screening assessments. Six articles reported outcomes following screening linked to preventative therapy in unselected populations of singleton pregnancies 26,28–32 . One study reported outcomes related to prophylactic therapy within a sub‐set of women who had screened high risk 27 ; this was matched with a subsequent publication regarding the screening outcomes of the same population to establish event rates across the entire unselected cohort 33 .…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 1102 studies, of which 47 were selected for full‐text evaluation. The inclusion criteria were met in 7 studies with a total of 377,790 participants 26–32 . Details of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations